2018
DOI: 10.1161/jaha.118.008675
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Changes in Fat and Lean Depots Following Weight Loss and Changes in Cardiovascular Disease Risk Markers

Abstract: BackgroundGluteofemoral fat mass has been associated with improved cardiovascular disease risk factors. It is not clear if loss of this protective fat during weight loss partially negates the effect of loss of visceral fat. The aim of this study was to examine regional fat loss in a large weight‐loss cohort from one center and to determine if fat loss in the leg and total lean tissue loss is harmful.Methods and ResultsWe combined the data from 7 of our previously published 3‐month weight‐loss studies and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, we did not observe a significant effect of GLP-1 RAs on reducing SBP and DBP among children and adolescents with obesity or overweight. An excess of fat tissue regardless of age and sex has been associated with increased blood pressure [40]; therefore, reductions in fat tissue may result in improvements in blood pressure and lipid profiles [41]. In this NMA, the effect of exenatide on total fat tissue reduction and blood pressure reduction was not significant [28,29].…”
Section: Discussionmentioning
confidence: 66%
“…In this study, we did not observe a significant effect of GLP-1 RAs on reducing SBP and DBP among children and adolescents with obesity or overweight. An excess of fat tissue regardless of age and sex has been associated with increased blood pressure [40]; therefore, reductions in fat tissue may result in improvements in blood pressure and lipid profiles [41]. In this NMA, the effect of exenatide on total fat tissue reduction and blood pressure reduction was not significant [28,29].…”
Section: Discussionmentioning
confidence: 66%
“…Thus, comparisons to studies using waist and hip circumferences are difficult. Previous weight-loss studies found larger changes in abdominal AT than in lower body AT (hip, leg, or gluteofemoral) [23,[54][55][56]. A study including an overfeeding/underfeeding protocol found that the upper body AT returned to pre-weight-gain levels more rapidly than lower body AT during underfeeding [57].…”
Section: Discussionmentioning
confidence: 96%
“…Another study mentions that both volume and quality of visceral and subcutaneous fat to metabolic risk including hypertension [34]. Other findings may not show the association of visceral fat and hypertension like in a 3-month weight-loss intervention study showed significant reduction in lean leg mass, instead of visceral fat, was positively associated with systolic blood pressure [35]. Another study concluded that waist circumference had an advantage over visceral fat thickness as an obesity index to identify components of metabolic syndrome that included hypertension [36].…”
Section: Discussionmentioning
confidence: 99%